MidSol3 - y=3x ( x' ) y' x (y) ( 0) 0 y= 1 _ 3 x In short,...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
y= x _ 1 3 _ y= 3 x ) ( 0 0 x' y' () x y () In short, we can write µ x y A 7→ µ x 0 y 0 B 7→ µ 0 0 . Since the matrix product BA corresponds to the composition of A followed by B ,we conclude BA µ x y = µ 0 0 , and BA must be the zero-matrix 0 , i.e. BA = µ 00 00 . 6. The transformation A maps an arbitrary point
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 04/12/2011 for the course MATH 33a taught by Professor Lee during the Fall '08 term at UCLA.

Ask a homework question - tutors are online